Fanvids : Television, Women, and Home Media Re-Use - Stevens, E. Charlotte (Transmedia (Amsterdam, Netherlands), 2020)
Fanvids, or vids, are short videos created in media fandom. Made from television and film sources, they are neither television episodes nor films; they resemble music videos but are non-commercial fanworks that construct creative and critical analyses of existing media. The creators of fanvids-called vidders-are predominantly women, whose vids prompt questions about media historiography and pleasures taken from screen media. Vids remake narratives for an attentive fan audience, who watch with a deep knowledge of the source text(s), or an interest in the vid form itself. Fanvids: Television, Women, and Home Media Re-Use draws on four decades of vids, produced on videotape and digitally, to argue that the vid form's creation and reception reveals a mode of engaged spectatorship that counters academic histories of media audiences and technologies. Vids offer an answer to the prevalent questions, What happens to television after it's been aired? How and by whom is it used and shared? Is it still television?